تقويم تحقق العدالة الضريبية في ظل طرق واساليب تقدير ضريبة الدخل: دراسة تطبيقية في الهيئة العامة للضرائب (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Tax justice is one of the important principles that any tax system seeks to achieve because it is an important and important pillar of the tax because it has negative repercussions on the tax accounting process on the one hand and the low tax revenues on the other hand. Therefore, countries have sought through their tax systems to use methods and methods In the process of estimating taxable incomes to achieve that justice depending on the awareness of their communities. The method adopted differs from one country to another according to the knowledge and understanding of the society of that state for taxation and its role in economic, social and political life. In Iraq, the General Authority for Taxation Methods of estimating taxable incomes in an attempt to reach real income and in line with the weak society's understanding of the tax understanding in Iraq, as it focused on adopting the method of estimation under the controls issued in estimating the tax income, despite the fact that it carries negative consequences that may not result in that income, The achievement of tax justice with the use of other methods through which to achieve that justice, which return positively to the taxpayer to pay the actual tax without increasing the one hand and the tax authority on the other hand by receiving the tax owed to the taxpayer without shortage, which leads to an increase in revenues Tax, which is poured into the state budget.